INFLUENCE OF MOBILE ROBOT CONTROL ALGORITHMS ON THE PROCESS OF AVOIDING OBSTACLES - Wójcicki, Piotr; Powroźnik, Paweł; Żyła, Kamil; Grzegórski, Stanisław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
This article presents algorithms for controlling a mobile robot. An algorithms are based on artificial neural network and fuzzy logic. Distance was measured with the use of ultrasonic sensor. The equipment applied as well as signal processing algorithms were characterized. Tests were carried out on a mobile wheeled robot. The analysis of the influence of algorithm while avoiding obstacles was made.